Impact of financial behavior on savings strategies among the poor in Vietnam - Anh, Nguyen The; Thu, Le Tai (Asian Development Policy Review, 2025)
This study focuses on improving the savings behavior of the poor in Vietnam, who face numerous challenges due to limited socio-economic conditions and inadequate access to formal financial services. The research employs a multivariable linear regression model to quantify the roles of income stability, financial literacy, access to banking services, health risks, social safety nets, and cultural norms. Data were collected through a quantitative survey ensuring representativeness and reliability. The analysis explores how these socio-economic factors interact to influence savings behavior. The results indicate a significant correlation between the above variables and the adoption of sound saving practices. Integrating financial and educational support for the Vietnamese poor, alongside a broader socio-economic perspective, plays a pivotal role in fostering better savings behavior. The study underscores the importance of socio-cultural contexts and appropriate financial incentives in enhancing the savings behavior of vulnerable groups. These findings offer insights for policymakers, financial institutions, and stakeholders in promoting financial inclusion, improving financial management literacy, and bolstering economic resilience among disadvantaged communities in Vietnam.